The relationship between employee involvement, psychological empowerment, and attitude towards organizational change in Malaysian Government-Linked Companies (GLCs) / Muhammad Afif Abdul Ghafar - Abdul Ghafar, Muhammad Afif (2017)
This research examined how employees in Malaysian GLCs perceived employee involvement, as well as their attitude towards organizational change. In addition, the relationship between employee involvement, psychological empowerment, and attitude towards organizational change was also examined. A mediation model was derived to further test whether psychological empowerment mediated the relationship between employee involvement and attitude towards organizational change. A convenience sample of employees was attained from seven Malaysian GLCs located across the Klang Valley. These GLCs were involved in a diverse range of industries which includes banking, telecommunication, utility, construction, plantation and automotive. A survey questionnaire which consisted of a (1) demographic profile, (2) Power, Information Sharing, Performance-Based Rewards, and Training Scale (PISPT), (3) Psychological Empowerment (PE) Scale, and (4) Attitude towards Change (ATC) Scale, was used to collect data. With a usable sample size of 313, it was found through descriptive statistics that overall, the employees in Malaysian GLCs had a positive perception of employee involvement and also attitude towards organizational change. Through inferential statistics in the form of correlation, regression, and bootstrapping method, the empirical results provided strong support for the positive relationship between employee involvement, psychological empowerment, and attitude towards organizational change. The results also supported the mediating role of psychological empowerment in the relationship between employee involvement and attitude towards organizational change. It is suggested that future research further test the conceptual framework utilized in the current study by utilizing longitudinal data to analyze the variables over a period of time, specifically, before and after the implementation of a specific organizational change initiative. Furthermore, organizational researcher could perhaps obtain qualitative data as a means to provide a deeper insight on the phenomena. Lastly, future study could opt to study specific attitude towards organizational, as opposed to a general attitude towards organizational change which the current study has focused on. The current study contributes to not only the literature, but also to the improvement of policy and practices to drive performance in Malaysian GLCs. From a theoretical standpoint, this research has provided empirical support on the mediating role of psychological empowerment, specifically between the relationship of employee involvement and attitude towards organizational change. In terms of attitude theory, this study has provided support on the uni-dimensional model of attitude towards organizational change. Also, this study further extends the validity of Kanter’s structural empowerment theory, as well as Lawler’s employee involvement model in a nonwestern context.